The Influence of Consumer–Brand Relationship on the Personalized Advertising Privacy Calculus in Social Media - Hayes, Jameson L.; Brinson, Nancy H.; Bott, Gregory J.; Moeller, Claire M. (Journal of interactive marketing, 2021)
Advertisers increasingly use personalized advertising that is tailored to consumers based on data concerning their preferences and behaviors, which is gained by collecting their personal information. The present study examines the role of consumer–brand relationships and social media platform contexts in effective personalized advertising. Consumers weigh the benefits of personalized brand information against forfeiting privacy by disclosing personal information. For the first time, a 2 (consumer–brand relationship: weaker/stronger) X 2 (data collection method: overt/covert) X 2 (platform: Facebook/Twitter) national online experiment was conducted to examine the personalization–privacy paradox in a social media context. The findings suggested that strong consumer–brand relationships affect the perceived value of information disclosure by bolstering the perceived benefits and mitigating perceived risks of disclosure whereas perceived risks dominated privacy calculus decisions when weak consumer–brand relationships were present. Theoretical and practical implications are discussed. •The personalized advertising privacy calculus was examined in the social media context.•Brand relationships bolster perceived value of information disclosure.•The presence of strong brand relationships helps mitigate perceived risks disclosure generating greater perceived value of information disclosure.•Greater perceived value of information disclosure leads to more willingness to have personal information used, and, thus, more positive advertising outcomes.